Tiers 1 and 2 of a German MTSS: impact of a multiple baseline study on elementary school students with disruptive behavior - Nitz, Jannik; Hagen, Tobias; Krull, Johanna; Verbeck, Leonie; Eiben, Katrin; Hanisch, Charlotte; Hennemann, Thomas (Frontiers in Education, 2023)
The prevalence of disruptive behavior is increasing worldwide, affecting the learning process and classroom climate, teacher-student relationships, and peer interactions. Disruptive behavior in childhood can have detrimental effects on a child's long-term growth and may predict similar behavior in adolescence and adulthood. Thus, it is not only contemporary education and school research that are concerned with addressing the issues of teacher workload reduction and improvement of students' learning environment, but it is also a socially relevant issue. The Multitiered Systems of Supports (MTSS) effectively mitigates some of these challenges in the education system and is recognized as a successful framework. Therefore, this single case study examined the first two tiers of an MTSS developed in Germany (Multimo) to determine the impact of its implementation on 32 students with disruptive behavior. The first hypothesis propose that the implementation of Tier 1 can effectively decrease disruptive behavior among all students and the second one that assigning students to Tier 2 can provide an additional reduction in disruptive behavior. Data analysis included multilevel analyses with piecewise-multilevel models and the overlap index, the Nonoverlap of All Pairs, based on teachers' direct behavior rating. All analyses focused exclusively on the outcome variable of disruptive behavior, which was estimated based on teachers' daily behavior ratings. The results of the study showed a significant reduction of disruptive behavior in elementary school students at Tier 1. Disruptive behavior decreased at Tier 2 as well but hat gelöscht: 5761 34 hat gelöscht: approach did not show a significant change compared with Tier 1. The study concludes that in the context of an MTSS, the Good Behavior Game and Daily Behavior Report Card can be used together.